Exploring educational simulation platform features for addressing complexity in Industry 4.0: a qualitative analysis of insights from logistics experts - Pacheco-Velazquez, Ernesto; Rodes-Paragarino, Virginia; Marquez-Uribe, Alberto (Frontiers in Education, 2024)
The emergence of Industry 4.0 brings transformative changes, integrating advanced technologies in industrial activities. While promising efficiency, these changes also introduce decision-making and logistical complexities challenging traditional models. This research identifies key characteristics of simulation platforms for addressing these complexities, especially in logistics education. Through qualitative analysis based on logistics experts' interviews, four main findings on educational games' role in Industry 4.0 logistics emerge. The articulated multidimensional model specifies adaptable technological characteristics, outlines educational objectives prioritizing operational knowledge and fostering collaboration, incorporates industry-specific elements, emphasizes user experience and reasoning for complexity. These findings guide the development of educational simulation platforms meeting Industry 4.0 demands, impacting educators, policymakers, and industry professionals by informing curriculum development and tool design. Complexities in decision-making models necessitate innovative tools for system evaluation, performance measurement, and human capital development. Classical paradigms lack the precision and adaptability needed in Industry 4.0 settings. Business simulation in higher education and employee training enhances decision-making and understanding of dynamic logistical scenarios. The study aims to examine simulation platforms' attributes addressing Industry 4.0 complexity, focusing on logistics. It seeks to replicate real-world processes, support decision-making on complex behaviors, scale to adapt to increasing complexities, ensure accessibility, ease of use, and integrate with Industry 4.0 technologies. Additionally, it extends implications into educational simulations, recognizing their importance in equipping the emerging workforce with essential Industry 4.0 skills. It provides practical recommendations for educators, policymakers, and industry professionals. The research aims to contribute to an integrated model for selecting, designing, and implementing educational simulation platforms meeting technical, pedagogical, and real-world demands of Industry 4.0 logistics. The study addresses two key questions: (1) Prioritized design elements and features by logistics experts for Industry 4.0 complexities in education. (2) Attributes and functionalities logistics experts suggest integrating into educational simulation platform designs for effective Industry 4.0 logistics preparation.